Associations between serum uric acid and depression in U.S. adults: An analysis of the national health and nutrition examination survey 2007–2016 - Ertao Zhang; Jie Li; Yan Liu; Zhao Dong; Longyu Wang; Can Zhao (PLoS ONE, 2025)
Limited research has specifically explored the gender-specific differences in relation to serum uric acid and depression. Therefore, the research aims to bridge that gap by exploring the relationships between serum uric acid and depression, stratified by gender, in U.S. adults. In this study, the participants comprised individuals from five consecutive survey cycles (NHANES 2007–2008–2015–2016), with 20,804 qualified participants incorporated into the research. The assessment of depression was conducted utilizing the Patient Health Questionnaire-9 (PHQ-9), and we calculated the weighted averages (95% CIs) for continuous variables and the percentages (95% CIs) for categorical variables among the chosen covariates. A multivariable logistic regression model with weights was utilized to assess the relationships between serum uric acid categories and depression status. In male subjects, uric acid levels may be linked inversely to depression. However, Tertile 3 (≥303.3 µmol/L) was more likely to develop depression than Tertile 1 (<249.8 µmol/L) among women. The study shows that high serum uric acid level may reduce the incidence of depression in men, but in females, it is an independent factor that increases the risk of depression.